Qualitative and quantitative analysis of talons of diurnal bird of prey - Mosto, María Clelia (2013)
The aim of this work is to establish qualitative and quantitative differences and similarities among talons lacking the keratin sheath in diurnal raptors. We set out to find a tool that allows for the determination of toe (I-IV) and hindlimb (left or right) identity. Different methodologies were used, such as classical anatomical descriptions and Fourier analysis of the medial contour of the ungual phalanx. A series of measurements and ratios were obtained and analysed using t-tests and principal components analysis. The qualitative descriptors are more important than quantitative analyses for assessing ungual phalanx identity. They allowed us to differentiate between hindlimbs and among toes corresponding to the talons of D-I, D-II and D-III, while the assignment of D-IV was complicated by its symmetry. The t-test showed that digits I and II did not differ in any measurement or ratio, whereas it showed several differences among the other digits. Fourier analysis was useful only when it was applied to one species with a large number of specimens. This work is an important contribution to the paleontological field where it is common to find isolated phalanges, and consequently, their identification is very difficult.